2005
DOI: 10.1016/j.janxdis.2003.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and construct validity of the Anxiety Sensitivity Index among island Puerto Ricans

Abstract: The factor structure and convergent and discriminant validity of the Anxiety Sensitivity Index (ASI) were examined among a sample of 275 island Puerto Ricans. Results from a confirmatory factor analysis (CFA) comparing our data to factor solutions commonly reported as representative of European American and Spanish populations indicated a poor fit. A subsequent exploratory factor analysis (EFA) indicated that a two-factor solution (Factor 1, Anxiety Sensitivity; Factor 2, Emotional Concerns) provided the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
(52 reference statements)
5
33
0
2
Order By: Relevance
“…More generally, the present article raises the question of whether cultural syndromes in other groups, especially panic attack-type cultural syndromes--e.g., ataque de nervios among Hispanic patients [Cintrón et al, 2005;Guarnaccia and Rogler, 1999;Hinton et al, in press b]--may also play a mediating role between general anxious-depressive distress and PTSD severity (and other types of psychopathology). Future studies should investigate whether this is true, and whether these cultural syndromes need to be specifically addressed in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the present article raises the question of whether cultural syndromes in other groups, especially panic attack-type cultural syndromes--e.g., ataque de nervios among Hispanic patients [Cintrón et al, 2005;Guarnaccia and Rogler, 1999;Hinton et al, in press b]--may also play a mediating role between general anxious-depressive distress and PTSD severity (and other types of psychopathology). Future studies should investigate whether this is true, and whether these cultural syndromes need to be specifically addressed in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The 16-item ASI rates, on 0-4 Likert-type scales, the degree of fear of anxietyrelated sensations [Reiss et al, 1986]. The Spanish version of the ASI has been validated [Cintró n et al, 2005;Sandin et al, 1996].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, research has shown that factors such as gender (Stewart, Taylor, & Baker, 1997), ethnicity , and anxiety disorders (Cintró n, Carter, Suchday, Sbrocco, & Gray, 2005;McNally, 2002) may influence AS and play important roles in AS relationships.…”
Section: Future Directionsmentioning
confidence: 99%